2023
DOI: 10.1055/a-2014-4634
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Abnormalities and Outcomes in Hospitalized Patients with COVID-19 Infection: A Cross-Sectional Study

Abstract: Thyroid gland can be affected by the COVID-19 infection. The pattern of thyroid function abnormality reported in COVID-19 is variable; in addition, some drugs used in COVID-19 patients like glucocorticoids and heparin can affect the thyroid function tests (TFT). We conducted an observational, cross-sectional study of thyroid function abnormalities with thyroid autoimmune profile in COVID-19 patients with varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…One study showed that more than one-third of patients with COVID-19 infection can have abnormal thyroid function test (TFT), more so in those with severe illness. The most common thyroid function abnormality was a sick euthyroid syndrome, irrespective of thyroid autoantibody status [22].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that more than one-third of patients with COVID-19 infection can have abnormal thyroid function test (TFT), more so in those with severe illness. The most common thyroid function abnormality was a sick euthyroid syndrome, irrespective of thyroid autoantibody status [22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified into different thyroid disorders, such as subclinical hypothyroidism, overt hypothyroidism, thyrotoxicosis, and non-thyroid illness, described in detail in the previous publication [46].…”
Section: Thyroid Functionmentioning
confidence: 99%
“…The effect of thyroid hormone supplementation on poor clinical outcomes for low thyroid hormone levels in critically ill patients is unknown. The clinical benefit of thyroid hormone supplementation has not been fully demonstrated 7,8 . On the contrary, some studies have reported that TH concentrations are not associated with clinical outcomes 9,10 .…”
Section: Introductionmentioning
confidence: 99%